2017
DOI: 10.1136/bmjspcare-2017-001355
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of a patient-reported outcome intervention in chronic heart failure

Abstract: Patients with chronic heart failure (CHF) have symptoms and concerns which are inadequately addressed. Patient-reported outcome measures (PROMs) can potentially improve the identification and management of advanced symptoms and palliative concerns. However, these have not been used in CHF.ObjectivesTo examine the feasibility and acceptability of using a PROM—the Integrated Palliative care Outcome Scale (IPOS)—together with heart failure nurse education and training to improve the identification and management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 54 publications
(61 reference statements)
3
83
0
1
Order By: Relevance
“…Both reviews aimed to appraise the general use of POS in the context and nature of its use and identify strengths and weaknesses of this patient reported outcome measure (23,26). The third study about the use of IPOS in advanced CHF (14), was identified by consulting the CHF group working at the Cicely Saunders Institute of Palliative Care, Policy and Rehabilitation, King's College London.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both reviews aimed to appraise the general use of POS in the context and nature of its use and identify strengths and weaknesses of this patient reported outcome measure (23,26). The third study about the use of IPOS in advanced CHF (14), was identified by consulting the CHF group working at the Cicely Saunders Institute of Palliative Care, Policy and Rehabilitation, King's College London.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of changes in emotional, social and spiritual wellbeing are described by this group of patients (13). However, these symptoms and other concerns are poorly recognised and addressed (14), both because of the reluctance to face deterioration and the lack of specialist knowledge in this final illness trajectory (15).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…POS is widely used in clinical care, audit, research, and training and it was validated in several languages (4,5). The POS measures have been used in different patients populations such as patients with cancer, respiratory, heart, renal or liver failure, and neurological diseases (6)(7)(8)(9)(10). POS-S was developed as an addition to POS to be used as a brief tool specifically focused on physical symptoms (11).…”
Section: Introductionmentioning
confidence: 99%